Analysis of Crossover Events and Allele Segregation Distortion in Interspecific Citrus Hybrids by Single Pollen Genotyping - Garavello, Miguel; Cuenca, José; Dreissig, Steven; Fuchs, Jörg; Navarro, Luis; Houben, Andreas; Aleza, Pablo (Frontiers in Plant Science, 2020)
In citrus, a classical method of studying crossovers and segregation distortion (SD) is the genetic analysis of progenies. A new strategy combining Fluorescence-Activated Cell Sorting and Whole Genome Amplification of haploid pollen nuclei with a large set of molecular markers, offers the opportunity to efficiently determine the frequency of crossovers and the identification of SD without the need to generate segregating populations. Here we have analyzed meiotic crossover events in a pollen nuclei population from `Eureka´ lemon and the allelic SD was evaluated in a pollen nuclei population from a clementine X sweet orange hybrid (`CSO´). Data obtained from the `CSO´ pollen nuclei population were compared to those obtained from genotyping of a segregating population (`RTSO´) arising from a hand-made sexual hybridization between diploid non apomictic selected tangor (mandarin X sweet orange; `RTO´ tangor) as female parent pollinated with `CSO´ tangor as male parent. The analysis of crossovers rates on chromosome 1 revealed the presence of up to five crossovers events on one arm and four on the corresponding other arm, with an average of 1.97 crossovers per chromosome while no crossover events were observed in five `Eureka´ lemon pollen nuclei. The rate of SD observed in `CSO´ pollen nuclei (13.8%) was slightly lower than that recovered in the `RTSO´ population (20.7%). In the pollen nuclei population, SD was found on linkage group (LG) 2, while the `RTSO´ population showed SD on LGs 2 and 7. Potential male gametic selection mechanisms were distinguished in pollen grains, while in the population, mechanisms of gametophytic selection and/or zygotic selection were observed. This methodology is a very useful tool to facilitate research focused on the reproductive biology of citrus and study the mechanisms that affect crossovers and SD.